2019
DOI: 10.4103/1735-5362.258485
|View full text |Cite
|
Sign up to set email alerts
|

Siamese neem flower extract suppresses cholesterol absorption by interfering NPC1L1 and micellar property in vitro and in intestinal Caco-2 cells

Abstract: Siamese neem (Azadirachta indica A. Juss var. siamensis Valeton ) ( A. indica ) leaf extract, a traditional ayurvedic medicine, has been reported to exhibit antipyretic, antibacterial, antidyslipidemic, and antihyperglycemia effects. This study investigated the mechanism of hypocholesterolemic effect of methanolic extract of Siamese neem flowers in in vitro studies and in Caco-2 cells. Pancreatic cholesterol esterase and 3-hydroxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…However, the protective potential of SF‐AE is in line with Duangjai et al. (2019) who showed that Azadirachta indica extract exerted, in vitro, a powerful lipid profile parameters regulatory activity.…”
Section: Discussionsupporting
confidence: 65%
“…However, the protective potential of SF‐AE is in line with Duangjai et al. (2019) who showed that Azadirachta indica extract exerted, in vitro, a powerful lipid profile parameters regulatory activity.…”
Section: Discussionsupporting
confidence: 65%
“…The content of compounds in neem can interfere with cholesterol absorption and inhibit de novo cholesterol synthesis (Duangjai et al, 2019). The content of alkaloids is able to inhibit the performance of lipase enzymes in the gastrointestinal tract so that fat absorption in the body is reduced (Budiarto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%